KALPA VRIKSHA IN THE GUPTA PERIOD: SYMBOLIC ANALYSIS, REPRESENTATION, AND CULTURAL INFLUENCE - Kumar, Manoj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Gupta period, hailed as the “Golden Age” in Indian history, witnessed extraordinary developments in art, religion, philosophy, and cultural expression. Within this flourishing civilization, the Kalpa Vriksha emerged as an important symbol signifying spiritual, cosmic, and social significance. This paper analyzes the profound role of the Kalpa Vriksha in Gupta art and spirituality, its manifestation in religious iconography, and its lasting influence on cultural views of cosmic unity, fertility, and divine order. Through artifacts, architectural carvings, and literary references, this research highlights the deep integration of the Kalpa Vriksha into Gupta culture.